Variations from morning to afternoon of middle cerebral and umbilical artery blood flow, and fetal heart rate variability, and fetal characteristics in the normally developing fetus. Issue 4 (13th December 2017) - Avitan, Tehila; Sanders, Ari; Brain, Ursula; Rurak, Dan; Oberlander, Tim F; Lim, Ken
Abstract: Objective: To determine if there are changes in maternal uterine blood flow, fetal brain blood flow, fetal heart rate variability, and umbilical blood flow between morning (AM) and afternoon (PM) in healthy, uncomplicated pregnancies. Study Design: In this prospective study, 68 uncomplicated singleton pregnancies (mean 35 + 0.7 weeks gestation) underwent a standard observational protocol at both 08:00 (AM) and 13:30 (PM) of the same day. This protocol included Doppler measurements of uterine, umbilical, and fetal middle cerebral artery (MCA) volume flow parameters (flow, HR, peak systolic velocity [PSV], PI, and RI) followed by computerized cardiotocography. Standard descriptive statistics, χ 2 and t tests were used where appropriate. P < .05 was considered significant. Results: A significant increase in MCA flow and MCA PSV was observed in the PM compared to the AM. This was accompanied by a fall in MCA resistance. Higher umbilical artery resistance indices were also observed in the PM compared to AM. In contrast, fetal heart rate characteristics, maternal uterine artery Doppler flow and resistance indices did not vary significantly between the AM and PM. Conclusion: In normal pregnancies, variations in fetal cerebral and umbilical blood flow parameters were observed between AM and PM independent of other fetal movements or baseline fetal heart rate. In contrast, uterine flow parameters remained stable across the day. These findings may have implications for the use of serial Doppler parameters used to guide clinical management in high‐risk pregnancies.